A construção da autoria compartilhada no universo da fanfiction - Barros, Maria Rita (2009)
This essay focuses on the production written by fans that use digital technology to upload their work, known in cyberspace as fanfics. These fans are anonymous people who submit their texts, their fanfics, to the screening of proofreaders and readers who united by the same literary taste and/or by the desire to improve their writing style feedback on, and take part in, each others´ work. A look at different cyber environments, particularly blogs and websites, reveals that fanfics have become a new type of textual creation. Our aim is to describe the universe within which fanfics, or fanfictions, exist so as to show how their shared authorship is built. Unlike school students, fanfic writers place themselves as the subject of their text, assume their authorship when they position themselves vis-a-vis a text, and, by making use of different genres, do not let the dialogue end. In order to penetrate the nature of such fans, who become authors themselves, or co-authors of an original work, we fall back on the observations made by theorists of Social Discourse Analysis. Our conclusion is that in cyberspace there is a new space for textual production, wherein it is possible to dialogue, (re) create, and for fanfics to present a smooth conception of authorship since they spring from an existing idea already accepted in the publishing universe and even by other media types. The fanfic writer places himself as a co-author of an original published work by getting hold of an idea that already exists, of a style, and starts a new game. Drawn by the voice of the original author, he seeks to emulate the same features, the same style, so as to find new players/readers who wish to share and discuss with him his authorship